2007
DOI: 10.1038/sj.bjc.6603750
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment with oxaliplatin and capecitabine in patients with advanced or metastatic oesophageal cancer: a phase II study

Abstract: This phase II study assessed the safety and efficacy of oxaliplatin and capecitabine in patients with advanced oesophageal cancer. Fiftyone eligible patients received oxaliplatin 130 mg m À2 intravenously on day 1 and capecitabine 1000 mg m À2 orally twice daily on days 1 to 14 in a 21-day treatment cycle as first-line treatment for advanced oesophageal cancer. Grade 3 neutropenia was seen in one patient and anaemia in another patient. No grade 4 haematological toxicities were observed. Grade 4 non-haematologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 23 publications
2
32
1
Order By: Relevance
“…A phase III study reported 47.9% objective response for patients treated with EOX; this difference in outcomes may be explained by the difference in number of patients treated in each study (16 and 244, respectively) (Cunningham et al, 2008). Some phase II studies that evaluated the efficacy of treatment with two drugs reported an overall RR of 42% on average (range: 35% to 65%) that is consistent with the value obtained in this study (Jatoi et al, 2006;Park et al, 2006;Van Meerten et al, 2007). This study was not designed to compare various treatment protocols, so these findings must be analyzed carefully.…”
Section: Discussionsupporting
confidence: 84%
“…A phase III study reported 47.9% objective response for patients treated with EOX; this difference in outcomes may be explained by the difference in number of patients treated in each study (16 and 244, respectively) (Cunningham et al, 2008). Some phase II studies that evaluated the efficacy of treatment with two drugs reported an overall RR of 42% on average (range: 35% to 65%) that is consistent with the value obtained in this study (Jatoi et al, 2006;Park et al, 2006;Van Meerten et al, 2007). This study was not designed to compare various treatment protocols, so these findings must be analyzed carefully.…”
Section: Discussionsupporting
confidence: 84%
“…There are few reports about this protocol used in esophageal cancer [12,13] . As a result of different pathological types, there have been some reports about combined treatment of oxalipatin and capecitabine for esophageal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been necessary to synthesize more selective and less reactive molecule. This led to platinum complexes of the second and third generation (28)(29)(30). Complexes of the second generation are structural analogs of cisplatin, designed to overcome the toxicity of cisplatin, while the third generation complexes were created as even more advanced analogues with the main task to act on tumor cells resistant to cisplatin.…”
mentioning
confidence: 99%